Improving Students' Mathematical Connection Skills Through The Think Talk Write (TTW) Type Cooperative Learning Model At Noemuti Public High School - Elisabeth Apmalo; Stanislaus Amsikan; Maria Naimnule (Program Studi Pendidikan Matematika, Fakultas Ilmu Pendidikan, Universitas Timor, 2026)
Abstract This research aims to improve students' mathematical connection skills through the application of a Think Talk Write (TTW) type cooperative learning model on quadratic function materials. This research is a Class Action Research conducted in two cycles, each of which includes holding planning, implementing actions, observation and reflection. The subjects in this study are 23 students of class X/A of Noemuti State High School. The data collection technique used mathematical connection ability tests and observation sheets of learning activities. The results of the study showed that in the first cycle the average score of students was 72.09 with classical completeness of 60.86. After learning improvements were made in the second cycle, the average student score increased to 84.22 with classical completeness reaching 100%. The results of the study show that the Think Talk Write model is able to improve learning activities, concept understanding and students' ability to connect various mathematical concepts. Thus, the Think Talk Write cooperative learning model is effectively used to improve students' mathematical connection skills on quadratic function material.